2012
DOI: 10.7763/ijbbb.2012.v2.131
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Garlic Homogenate Co-Administered with Anti-Tuberculosis Drugs in RatLiver Enzymes

Abstract: Abstract-The aim of this work is to evaluate the hepatoprotective effect of garlic homogenate co-administered with anti-tuberculosis drugs on the liver. Twenty rats were divided into five groups (each of four rats) designated A, B, C, D and E (control). 51.4mg/kg body weight of first line tuberculosis drugs (Isoniazid, Rifampicin, Pyrazinamide and ethambutol) was administered orally to two (2) rats in group A, B, C, and D for seven (7) days and the remaining two rats in each group for twenty-eight (28)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Previous studies indicated that garlic homogenates showed hepatoprotective activity in mice treated with Isoniazid. 15 Diallyl sulfides were also reported to have a protective effect, in vivo, on carbon tetrachloride-induced liver injury in mice. 16 Thus, it was expected for the polysulfide mixtures (G1 to G6) to show a hepatoprotective effect against acetaminophen toxicity.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…Previous studies indicated that garlic homogenates showed hepatoprotective activity in mice treated with Isoniazid. 15 Diallyl sulfides were also reported to have a protective effect, in vivo, on carbon tetrachloride-induced liver injury in mice. 16 Thus, it was expected for the polysulfide mixtures (G1 to G6) to show a hepatoprotective effect against acetaminophen toxicity.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…The main indicators suggesting the improved condition of liver cells were decreased levels of enzymes: Alanine Transaminase (ALT), Alkaline Phosphatase (ALP) and Aspartate Transaminase (AST) observed after co‐administration of plant extracts with anti‐TB drugs in animal models. Such effect was observed for Garlic ( Alium sativum ) homogenate in rats [48], standardized aqueous onion ( Alium cepa ) extract in rats [49], standardized alcoholic extract from Terminalia chebula fruit containing 0.250% chebuloside in rats [50], sylimarin isolated from milk thistle ( Sylibum marianum ) in rats [51] and in rabbits [52], as well as for nanoparticle‐formulated curcumin which significantly reduced liver lesions induced by INH as confirmed by lowering liver enzyme levels in mice [53]. Decreased levels of liver enzymes suggested the reduction of oxidative stress in liver cells [48].…”
Section: Plant‐based Food Products Used For Reduction Of Side Effects...mentioning
confidence: 90%
“…As explained in various studies that garlic has anti-mycobacterium activities. Mycobacterium tuberculosis is the most sensitive and rapidly died (Nasiru et al, 2012;Rao et al, 1946).…”
Section: Effect Of Garlic On Human Stomach: Helicobactermentioning
confidence: 99%